Toward a common understanding of competencies for health technology assessment: enhancing educational and training programs around the globe. (7th December 2020) - Mueller, Debjani; Gutierrez-Ibarluzea, Iñaki; Chiumente, Marco; Oortwijn, Wija
Abstract: Background: Depending on the health system context and the demands of relevant stakeholders in countries, the need, organizational structure, and prerequisites for enabling capacity building and development in health technology assessment (HTA) will vary. Core competencies are instrumental in this and include essential knowledge, skills, and attitudes (KSAs). They provide building blocks for delivering high-quality and effective practices of HTA. We aimed to systematically explore and develop an overview of the core competencies necessary for HTA. Methods: This study was conducted during 2016–19 using different methods in a structured manner. We drew concepts of KSAs from various literature sources, surveyed universities and HTA professionals, and conducted expert workshops to arrive at a common understanding of the required competencies. Results: The terminology for KSAs defining competencies in HTA programs has been clarified. In addition, a list of competencies offered through different educational and training programs has been created. The surveys provided clarity on a common understanding of KSAs among HTA stakeholders. Thereafter, a set of competencies was described and classified according to the HTA domains. Conclusions: Our study shows that there is diversity in HTA programs offered by educational institutions. The content of the programs varies due to differences between countries regarding the level of HTA development and the need for HTA, including the understanding of what HTA is. The preparation of a competency checklist or a "menu" of options mirroring the diversity of HTA will ensure that the specific needs of the HTA community will be covered.